2014
DOI: 10.1186/s12967-014-0303-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the caspase-dependent mitochondrial apoptotic pathway in mononuclear cells of patients with systemic lupus erythematosus

Abstract: BackgroundThis study aimed to explore the role of apoptosis initiators, caspase-9, caspase-10, mitochondrial anti-viral signaling protein (MAVS), and interferon regulatory factor 7 (pIRF7), in patients with systemic lupus erythematosus (SLE).MethodsLeukocyte apoptosis was determined by flow cytometry, including annexin V, APO2.7, and 7-amino-actinomycin D (7-AAD) on each subtype of leukocyte in 35 patients with SLE, 15 disease controls, and 17 volunteer normal controls. Levels of caspase-9, caspase-10, MAVS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Besides, mitochondrial (mt)DNA damage [45,73,74,75,76], characterized by D-310 heteroplasmy and copy number decrease [42,77], is also present in SLE. Su et al [78] investigated the caspase-dependent mitochondrial apoptotic pathway in immune cells from SLE patients. They found that peripheral blood mononuclear cells (PBMCs) and polymorphonuclear neutrophils (PMNs) from SLE patients exhibited increased expression of apoptosis initiators, caspase 9 and 10, that are positively correlated to the expression of mitochondrial anti-viral signaling protein and interferon regulatory factor 7.…”
Section: Mitochondrial Dysfunction Is One Of the Crucial Up-streammentioning
confidence: 99%
“…Besides, mitochondrial (mt)DNA damage [45,73,74,75,76], characterized by D-310 heteroplasmy and copy number decrease [42,77], is also present in SLE. Su et al [78] investigated the caspase-dependent mitochondrial apoptotic pathway in immune cells from SLE patients. They found that peripheral blood mononuclear cells (PBMCs) and polymorphonuclear neutrophils (PMNs) from SLE patients exhibited increased expression of apoptosis initiators, caspase 9 and 10, that are positively correlated to the expression of mitochondrial anti-viral signaling protein and interferon regulatory factor 7.…”
Section: Mitochondrial Dysfunction Is One Of the Crucial Up-streammentioning
confidence: 99%
“…This study linked mir-150-5p with intracellular MAVS protein expression. The MAVS protein levels were significantly higher in patients with lupus than in normal controls and were negatively correlated with lupus activity in our previous study [ 30 ]. The dynamic changes of mir-150-5p relating to lupus activity are worthy of further investigation.…”
Section: Discussionmentioning
confidence: 85%
“…This observation suggests the activation of the extrinsic apoptotic caspase-10-related pathway in SLE [ 22 , 39 ] and that caspase-10 is influenced by microRNA, which could be reflected by plasma microRNA levels in this study. Furthermore, we previously demonstrated that caspase-10 positively correlates with pIRF7, and caspase-9 and caspase-10 both positively correlate with each other, pIRF7, and MAVS 70 kD [ 30 ], indicating that interferons are links to cellular apoptosis and anti-virus immunity in SLE [ 16 , 40 42 ]. The pathways of MAVS and caspase-10 were examined by detecting plasma microRNA in SLE ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature also contains data that indicate quite the opposite. For instance, a negative correlation was found between caspase‐9 levels and disease activity in patients with systemic lupus erythematosus (SLE), an autoimmune disease, in a study conducted by Yu‐Jih Su et al Rastin et al conducted a case‐control study investigating T lymphocyte apoptosis in 35 patients with SLE and found that caspase‐8 and caspase‐9 levels were lower in female patients as compared to the control group . As it is also apparent here, especially the caspase family has a role in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%